TAX POLICIES THAT SUPPORT INNOVATION COMPETITIVENESS OF SMALL BUSINESSES IN INDONESIA - Heru Kreshna Reza; Cristofer Sumiok; Loso Judijanto; Melly Susanti (Juremi: Jurnal Riset Ekonomi, 2025)
This study examines the impact of tax policy, competitive challenges, access to capital, and tax digitalization on the growth of MSMEs in Indonesia. The reduction of the Final Income Tax (PPh) rate and the exemption of PPh for entrepreneurs with a turnover of up to IDR 500 million per year have eased the financial burden of MSMEs and increased their production capacity. However, cartel and monopoly practices remain an obstacle to business competition. While the Kredit Usaha Rakyat (KUR) program improves access to capital, information about the program should be expanded, especially in remote areas. While not all MSMEs are ready to adopt the technology, the digitization of the tax system such as e-Filing and e-Invoicing has improved the efficiency and transparency of the taxation process. The main barriers that require further education and socialization are low levels of tax compliance and limited access to information. Policy recommendations include expanding tax incentives, improving access to capital, enforcing laws against cartels and monopolies, and supporting digitalization and education. With the right policy support, MSMEs can develop into a stronger economic backbone, contributing more to the national economy and community welfare.